Efficacy of Cryotherapy as a Primary Endoscopic Ablation Modality for Dysplastic Barrett’s Esophagus and Early Esophageal Neoplasia: A Systematic Review and Meta-Analysis - Raseen Tariq MD; Sarah Enslin PA; Maham Hayat MD; Vivek Kaul MD (Cancer Control, 2020)
Introduction: Cryotherapy is a cold-based ablative therapy used primarily as second line therapy in patients with Barrett’s esophagus (BE) who have persistent dysplasia after undergoing endoscopic treatment with radiofrequency ablation (RFA). Few studies have described the use of cryotherapy as a primary treatment modality for dysplastic or neoplastic BE. Aim: To evaluate the efficacy of cryotherapy as primary treatment of dysplastic and/or neoplastic BE by conducting a systemic review and meta-analysis. Methods: A systematic search of Medline, Embase, and Web of Science was performed from January 2000 through March 2020. Articles included were observational studies and clinical trials which included patients who had biopsy confirmed dysplastic or neoplastic BE (i.e., high grade dysplasia (HGD), low grade dysplasia (LGD) or intramucosal adenocarcinoma (ImCA)), underwent ≥1 session of cryotherapy, and had a follow-up endoscopy. Primary outcomes were pooled proportions of patients achieving complete eradication of dysplasia (CE-D) and/or intestinal metaplasia (CE-IM) by using a random effects model. Results: Fourteen studies making up 405 patients with follow-up ranging from 3-54 months were included. In 13 studies, a total of 321/405 patients achieved CE-D with a pooled proportion of 84.8% (95% confidence interval [CI] 72.2-94.4), with substantial heterogeneity (I 2 = 88.3%). In 13 studies, a total of 321/405 patients achieved CE-D with a pooled proportion of 84.8% (95% confidence interval [CI] 72.2-94.4), with substantial heterogeneity (I 2 = 88.3%). Subgroup analysis of only high-quality studies revealed a pooled proportion of CE-D 91.3% (95% CI, 83.0-97.4, I 2 = 69.5%) and pooled proportion of CE-IM of 71.6% (95% CI, 59.0-82.9, I 2 = 80.9%). Adverse events were reported in 12.2% patients. Conclusion: Cryotherapy is a safe and effective primary therapy for dysplastic/early neoplastic BE. CE-D and CE-IM rates are comparable to those for other ablation modalities, including RFA. Cryotherapy should be considered for primary therapy of dysplastic BE and early esophageal neoplasia.